Management and Contingency Planning for Oil Spill in the Niger Delta Region of Nigeria - Yoseph, Eshetu; Ersino, Wondimu; Alemu, Kebede (International Journal of Social Sciences: Current and Future Research Trends, 2025)
Restricted Access.